Control de la contaminación ambiental en laconstrucción de los túneles del cerro “san eduardo” de la ciudad de guayaquil - Espín Alarcón, Guillermo Enrique (Revista Universidad de Guayaquil, 2002)
The present work is in construction in the city of Guayaquil, the road project Tunnels of the Hill San Eduardo, includes/understands 2300 meters linear of tunnel and 1100 meters linear of routes of access to the project; which is divided infour mouths as have three tracks of circulation each one. The used constructive method in the construction is denominated the New Austrian Method of Construction of Tunnels; which produces more of million cubic meters approximately of excavation and evacuation. In the construction of the tunnels four perforator’s Jumbos of three arms were used, dynamite, near one hundred twenty dumps, sent concrete, and more than five hundred people including technical personnel and working. In the routes of access and adjustment of slopes they were excavated more than three million cubic meters. The Plan of Environmental Handling considers like product of these constructive operations, a generation of environmental contamination in the interior and outside of the tunnels;and it stipulated that they must be controlled through stations of monitored of environmental parameters: noise, particulate material and gases. These obtained measurements do not have to surpass theexisting environmental parameters in the effective Ecuadorian Legislation. In case of obtaining values allowed or superior to the Ecuadorian environmental norm not to mitigate the impacts applying the Plan of Handling.